Mental health status of pregnant and breastfeeding women during the COVID‐19 pandemic—A multinational cross‐sectional study. (13th February 2021) - Ceulemans, Michael; Foulon, Veerle; Ngo, Elin; Panchaud, Alice; Winterfeld, Ursula; Pomar, Léo; Lambelet, Valentine; Cleary, Brian; O'Shaughnessy, Fergal; Passier, Anneke; Richardson, Jonathan L.; Hompes, Titia; et al.
Abstract: Introduction: Evidence on perinatal mental health during the coronavirus disease 2019 (COVID‐19) pandemic and its potential determinants is limited. Therefore, this multinational study aimed to assess the mental health status of pregnant and breastfeeding women during the pandemic, and to explore potential associations between depressive symptoms, anxiety, and stress and women's sociodemographic, health, and reproductive characteristics. Material and methods: A cross‐sectional, web‐based study was performed in Ireland, Norway, Switzerland, the Netherlands, and the UK between 16 June and 14 July 2020. Pregnant and breastfeeding women up to 3 months postpartum who were older than 18 years of age were eligible. The online, anonymous survey was promoted through social media and hospital websites. The Edinburgh Depression Scale (EDS), the Generalized Anxiety Disorder seven‐item scale (GAD‐7), and the Perceived Stress Scale (PSS) were used to assess mental health status. Regression model analysis was used to identify factors associated with poor mental health status. Results: In total, 9041 women participated (including 3907 pregnant and 5134 breastfeeding women). The prevalence of major depressive symptoms (EDS ≥ 13) was 15% in the pregnancy cohort and and 13% the breastfeeding cohort. Moderate to severe generalized anxiety symptoms (GAD ≥ 10) were found among 11% and 10% of the pregnant and breastfeeding women. The mean (±SD) PSS scores for pregnant and breastfeeding women were 14.1 ± 6.6 and 13.7 ± 6.6, respectively. Risk factors associated with poor mental health included having a chronic mental illness, a chronic somatic illness in the postpartum period, smoking, having an unplanned pregnancy, professional status, and living in the UK or Ireland. Conclusions: This multinational study found high levels of depressive symptoms and generalized anxiety among pregnant and breastfeeding women during the COVID‐19 outbreak. The study findings underline the importance of monitoring perinatal mental health during pandemics and other societal crises to safeguard maternal and infant mental health.